(untitled) (Nigerian Journal of Technology, 2016)
Compression test was conducted on packaged common tomatoes in Nigeria (Roma VF) to study the effects of size and load configuration in terms of the fruits axes, deformation and stress at break and yield point of the fruits due to static loading. Different sizes of tomato were selected and ranged as big, medium sized, and small sized tomato. The bigger sizes were grouped as the A class, while the medium sizes were grouped as B class, and the smaller sized as C class. The samples were further classified as A1, A2, B1, B2, C1 and C2. While all samples having the suffix 1 were subjected to axial loading, the ones with 2 were subjected to radial loading under the Instron Universal Compression Testing Machine at the stress rate of 0.002 MPa. The study shows that majority of the samples tends to withstand higher force axially than radially for bigger and medium sized. But for the smaller tomato ranging from 35mm and below, the material was able to withstand high pressure force radially than axially before yielding. http://dx.doi.org/10.4314/njt.v35i4.35